2022
DOI: 10.1007/s12010-022-04132-y
|View full text |Cite
|
Sign up to set email alerts
|

Critical Review on Nutritional, Bioactive, and Medicinal Potential of Spices and Herbs and Their Application in Food Fortification and Nanotechnology

Abstract: Medicinal or herbal spices are grown in tropical moist evergreen forestland, surrounding most of the tropical and subtropical regions of Eastern Himalayas in India (Sikkim, Darjeeling regions), Bhutan, Nepal, Pakistan, Iran, Afghanistan, a few Central Asian countries, Middle East, USA, Europe, South East Asia, Japan, Malaysia, and Indonesia. According to the cultivation region surrounded, economic value, and vogue, these spices can be classified into major, minor, and colored tropical spices. In total, 24 trop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 813 publications
2
40
0
Order By: Relevance
“…Tsuda et al 37 similarly agree that curcumin has anti-obesity/anti-adipogenic and anti-diabetes biological properties among others, as also observed by Labban et al 38 and can be seen to have a high probability of preventing or reducing the magnitude of various obesity states through well defined biochemical signaling pathways and others that may be active even on preadipocytes, 39 as well as in reversing or modulating age and obesity associated metabolic diseases. 16,40 Most noteworthy is that it has also been shown that curcumin is a bioactive compound that may not only have multiple beneficial health and anti-oxidative effects, 41 but a beneficial effect on the course of SARS-CoV-2 infection and that might hence be helpful in the prevention of long-COVID complications-and others that are closely associated with cardiovascular diseases and obese states. 42,43 Dietary curcumin supplementation may also promote health in general, 4 while helping promote white adipose tissue browning found in obese states.…”
Section: Resultsmentioning
confidence: 99%
“…Tsuda et al 37 similarly agree that curcumin has anti-obesity/anti-adipogenic and anti-diabetes biological properties among others, as also observed by Labban et al 38 and can be seen to have a high probability of preventing or reducing the magnitude of various obesity states through well defined biochemical signaling pathways and others that may be active even on preadipocytes, 39 as well as in reversing or modulating age and obesity associated metabolic diseases. 16,40 Most noteworthy is that it has also been shown that curcumin is a bioactive compound that may not only have multiple beneficial health and anti-oxidative effects, 41 but a beneficial effect on the course of SARS-CoV-2 infection and that might hence be helpful in the prevention of long-COVID complications-and others that are closely associated with cardiovascular diseases and obese states. 42,43 Dietary curcumin supplementation may also promote health in general, 4 while helping promote white adipose tissue browning found in obese states.…”
Section: Resultsmentioning
confidence: 99%
“…92 The encapsulation of quercetin in biopolymeric nanoparticles can also enhance its therapeutic value. 93 At present, the use of chitosan nanoparticles is a research hotspot, and in vitro and in vivo studies on animals have demonstrated that using chitosan nanoparticles to encapsulate quercetin may exert a better effect on tumors. 94 Besides, quercetin can be incorporated into the backbone of the polymer matrix, which allows a slow release of the guest polyphenol.…”
Section: Delivery Systems For the Enhancement Of Quercetin Bioavailab...mentioning
confidence: 99%
“…Curcumin (CUR), an orange-yellow hydrophobic polyphenol derived from the rhizomes of the herb Curcuma longa, is another natural bioactive and therapeutic compound due to its anticarcinogenic, antibacterial, antimicrobial, antifungal, antiviral, antimalarial, antioxidant, antimutagenic, cicatrizing, anti-inflammatory, anti-coagulant, anti-fertility, antiprotozal, antifibrotic, antivenom, antiulcer, hypotensive, and anticholesteremic properties, as well as its free-radical effects [3,5,[22][23][24]. Because of its flavoring properties, CUR is used as a food coloring, and as a traditional medicine in India and China for the treatment and prevention of several diseases, such as neurological, oncological, autoimmune, metabolic, cardiovascular, and diabetes, due to its extraordinary activities [3][4][5]23], which have attracted increasing interest from researchers to CUR [25]. However, the use of CUR in therapeutic applications has been limited due to its poor bioavailability and water solubility [4,26,27].…”
Section: Preparation Of the Cs-and Cs-cur-based Macrobeadsmentioning
confidence: 99%